The Nursing Effect of Individualized Management on Patients With Diabetes Mellitus Type 2 and Hypertension - Li, Ran; Xu, Weiwei; Yang, Ping; Tan, Lian; Ling, Zhiyu; Gan, Xiuni (Frontiers in Endocrinology, 2022)
It focused on clinical effects of individualized nursing and health education (INHE) on patients with diabetes mellitus type 2 (T2DM) and hypertension. 68 patients were randomly rolled into two groups, 34 cases in the control group (group A) received routine nursing and remaining 34 cases in the experimental group (group B) received INHE. The disease knowledge mastery (DKM) and the effect of rehabilitation nursing of patients were compared. The results suggested that DKM of patients in group B was obviously greater (P < 0.05). The total effective rate (TER) in group B was 91.45%, which was observably greater than that (76.35%) in group A (P < 0.05). After nursing, the fasting plasma glucose (FPG), 2-hour postprandial glucose (2h PG), systolic blood pressure (SBP), and diastolic blood pressure (DBP) levels of all patients decreased, and those in group B were much lower (P < 0.05). Scores of the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) of the two groups were 56.34 ± 8.12 points and 56.33 ± 8.01 points in group A, respectively; and those in group B were 42.52 ± 6.77 points and 41.71 ± 7.23 points, respectively; and they were all decreased and those in the group B were obviously smaller (P < 0.05). In summary, INHE can effectively improve the psychological cognition of patients with T2DM and hypertension and strengthen the control of blood pressure and blood sugar.